Neuroprotective effect of ranolazine in mice's model of Alzheimer's disease - Mariam H. Sadiq; Adeeb A. Al-Zubaidy; Nawres L. Wahhab (Romanian Journal of Neurology, 2024)
Background. Alzheimer's disease is a neurodegenerative disorder that worsens over time as more brain regions are affected and symptoms increase. It usually starts slowly and advances permanently. Ranolazine is a piperazine derivative used as a second-line treatment for people with chronic aortic stenosis who are unresponsive to other medications and have steady or ineffectively-managed angina pectoris. This study is intended to look into the possible neuroprotective effects of ranolazine scopolamine-induced Alzheimer's illness-like features in a mouse model. Methods. This is a randomized controlled animal study that has been carried out in Department of Pharmacology from College of Medicine of Al-Nahrain University. Mice were separated into five groups equally (each group with 10); a control group, and an induction group (mice were administered scopolamine 1 mg per kg intraperitoneally every 24 hr for seven days to induce features similar to Alzheimer's disease). The mice in the remaining three treatment groups were given tested medications prophylactically for 14 days, then the induction was carried out with scopolamine 1 mg/kg i.p. once daily while the tested medication dosages were continued for an additional 7 days; these treatment groups included: donepezil group (5 mg/Kg/d), ranolazine group (40 mg/Kg/d), and combination groups - donepezil (5 mg/Kg/d) with ranolazine (40 mg/Kg/d); all were administrated i.p. once daily. Behavioral parameters including the Y maze test and novel object recognition test were assessed for inflammatory cytokines and oxidative stress parameters. Result. Ranolazine exhibits significant improvement in behavior and memory, oxidative stress parameter level, as well as inflammatory cytokines. When the scopolamine induction group was compared to the control group, the spontaneous alteration considerably decreased (p ≤0.001). However, compared to the induction group, all three donepezil, ranolazine, and combination (donepezil + ranolazine) groups had a highly significant increase in the spontaneous alteration and when compared with the control group, there were no statistically significant changes (p >0.05). In comparison with a control group, the scopolamine (induction group) revealed a highly significant reduction (p ≤0.001) in the recognition index. In contrast to the induction group, all three donepezil, ranolazine, and combination (donepezil + ranolazine) groups demonstrated a highly statistically significant improvement in the recognition index. When compared with the control group, there were no statistically significant changes (p >0.05). Conclusion. The current investigation demonstrated ranolazine's neuroprotective action against scopolamine-induced AD-like characteristics in mouse models. The present work has demonstrated the considerable antioxidant and anti-inflammatory benefits of ranolazine, which may account for these positive results.